Weathered antlers as a source of DNA - Roy G. Lopez; Paul Beier (Wildlife Society Bulletin)
Abstract We tested antlers of Coues white‐tailed (Odocoileus virginianus couesi) and mule deer (O. hemionus) in various stages of natural decomposition to determine the degree of weathering that cast antlers could endure and still yield usable DNA. Based on physical characteristics, we partitioned antlers into 7 weathering categories ranging from freshly cast (class 1) to having been exposed to weathering for ≥8 years (class 7). Most antlers that had weathered 1–7 years yielded amplifiable DNA, whereas antlers weathered for ≥8 years failed to yield replicable DNA. This study confirms that antlers exposed to weathering for 1–7 years can be a source of replicable DNA and, thus, contribute an additional, and previously overlooked, non‐invasive sample for analysis in molecular genetics studies. Published 2012. This article is a U.S. Government work and is in the public domain in the USA.